THE EFFECT OF PRODUCT QUALITY AND PRODUCT IMAGE ON CUSTOMER PURCHASE INTENTION: A SYSTEMATIC LITERATURE REVIEW - Islamiyati, Husnaawati Fauziyyah; Milenia, Nimas Aura Husna; Fauzi, Khoiron; Jaelani, Meta Humaira (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study explores the impact of product quality on customer satisfaction and loyalty, focusing on three variables: product quality, product quality, and customer loyalty. It aims to understand how these variables influence consumer behavior and provides insights for international manufacturers on improving their product quality strategies. The research also explores the influence of economic needs, psychological factors, social factors, and situational factors on consumer behavior. Consumers prioritize product quality when buying a product at a certain price, and social factors, such as media interactions, play a crucial role in understanding consumer behavior. The increasing prevalence of online shopping has led to consumers using various products to compare product quality. The study reveals that 67% of consumers in Kelantan, especially in Kota Bharu, are influenced by factors such as price, product quality, service, reputation, and product knowledge, contributing to 50% of their purchasing decisions. Product quality is crucial in e-commerce, as it affects customer satisfaction and loyalty. Product image and brand authenticity play a significant role in stimulating purchase intentions in adults.